Evaluasi Program Keluarga Berencana pada Era Desentralisasi di Kuningan Jawa Barat - Suparman, Nanang; Sakti, Fadjar Tri; Engkus, Engkus (Universitas Medan Area, 2018)
The Family Planning Program (KB) run by the Kuningan district government is an important part of the implementation of good governance so it is feasible to be evaluated to find out the achievement of the program to establish a prosperous small family through caring and community participation in the maturity aspects of marriage, birth control, and fostering family resilience, which has a positive effect on the Human Development Index (HDI). This study analyzes four aspects of evaluation according to the CIPP evaluation model (Context Input Process Poduct), which includes aspects i) context evaluation; ii) evaluation of inputs; iii) process evaluation; and iv) product evaluation. This study uses a descriptive-qualitative method with primary data in the form of interviews and secondary data in the form of relevant documents. The results showed the active role of the community / volunteer groups in family planning services, the availability of human resources, funding, time of implementation, but in the absence of indicators of success, the absence of SOPs on process evaluation and product evaluation could not be a clear input. in the cycle of the overall family planning program.